2010
DOI: 10.1002/app.32807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MgAlCe‐CO3 layered double hydroxides on the thermal stability of PVC resin

Abstract: MgAlCe-CO 3 layered double hydroxides (LDHs) with different Ce/Al molar ratios were prepared by the constant pH coprecipitation method. The synthesized materials were characterized by XRD and FTIR, and the results showed that the hydrotalcite-like materials have a layered structure. Different LDHs as stabilizers were mixed with PVC resin. The tests of thermal aging and Congo red for the PVC composites were carried out at 180 6 1 C, respectively. The results showed when MgAlCe-CO 3 -LDHs were added into PVC as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…The hydrated tin(IV) oxide shows a broad (Sn)O–H stretching band with lower absorption compared with MHS, and no peak at 1167 cm −1 can be identified. The spectrum for ‘LDH’ is also similar to that reported previously . The broad peaks around 3483 and 1365 cm −1 can be ascribed to (Mg/Al)O–H stretching and anti‐symmetric vibration of CO 3 2− , respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The hydrated tin(IV) oxide shows a broad (Sn)O–H stretching band with lower absorption compared with MHS, and no peak at 1167 cm −1 can be identified. The spectrum for ‘LDH’ is also similar to that reported previously . The broad peaks around 3483 and 1365 cm −1 can be ascribed to (Mg/Al)O–H stretching and anti‐symmetric vibration of CO 3 2− , respectively.…”
Section: Resultssupporting
confidence: 83%
“…In contrast, layered double hydroxides (LDHs), sometimes referred to as hydrotalcite‐like compounds, can stabilize PVC, acting as hydrogen chloride scavengers . It has been recently reported that an LDH caused initial colour change when used as a stabilizer alone, but remarkable improvement in thermal stability of PVC was achieved when used in combination with a Ca/Zn stabilizer . It has also been reported that LDH facilitated the dehydrochlorination of PVC but promoted char formation, which was beneficial for flame retardancy .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the Mg/Al/Nd and Mg/Al/Sm LDH samples did not show any luminescence. Recently, the organic-inorganic hybrid phosphors have been designed and assembled by the intercalation of organic compounds, as sensitizer, into the layered lanthanide hydroxides or by changing the doping concentration of the activator ions [13][14][15][16][17]. This approach is currently under investigation to stimulate light emission in the Mg/Al/Nd and Mg/Al/Sm LDH samples.…”
Section: Resultsmentioning
confidence: 99%
“…eir results showed that ZnAlLa-CO 3 LDH could significantly enhance the thermal stability of PVC samples. For another rare earth element, cerium (Ce), Yi et al [13] prepared MgAlCe-CO 3 LDH and as stabilizer for PVC resin.…”
Section: Introductionmentioning
confidence: 99%